2015
DOI: 10.1111/dar.12264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of neck injection among people who inject drugs in Tijuana, Mexico

Abstract: Introduction and Aims Injecting drugs in the neck has been related to adverse health conditions such as jugular vein thrombosis, deep neck infections, aneurysm, haematomas, airway obstruction, vocal cord paralysis and wound botulism, among others. We identified prevalence and correlates of neck injection among people who inject drugs (PWID) in Tijuana, Mexico. Design and Methods Beginning in 2011, PWID aged ≥18 years who injected drugs within the last month were recruited into a prospective cohort. At baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
2
13
1
Order By: Relevance
“…In this Canadian study, injection into the jugular vein was associated with daily injection and the authors hypothesized that venous access difficulties were likely to occur among people engaging in high frequency injecting drug use (Hoda, et al, 2008). Frequent injection (that is injecting more than once daily) was also associated with jugular vein injection in Tijuana (Rafful, et al, 2015), and in both the Canadian and Mexican studies people who had injected into their jugular vein were more likely to require or seek assistance with injecting (Hoda, et al, 2008;Rafful, et al, 2015). In a national study undertaken in Iran in 2007, 12% of people who injected heroin daily or more frequently reported their neck as their usual injection site (Karimi, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this Canadian study, injection into the jugular vein was associated with daily injection and the authors hypothesized that venous access difficulties were likely to occur among people engaging in high frequency injecting drug use (Hoda, et al, 2008). Frequent injection (that is injecting more than once daily) was also associated with jugular vein injection in Tijuana (Rafful, et al, 2015), and in both the Canadian and Mexican studies people who had injected into their jugular vein were more likely to require or seek assistance with injecting (Hoda, et al, 2008;Rafful, et al, 2015). In a national study undertaken in Iran in 2007, 12% of people who injected heroin daily or more frequently reported their neck as their usual injection site (Karimi, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have investigated injection into the jugular vein have reported substantial differences in the prevalence of this practice. In a recent study in Tijuana (Mexico) one third of PWID reported that the neck was the main site used for injection in 2011 (Rafful, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in our study were engaging in high-risk polydrug use. Evidence suggests, even when compared to other types of illicit drug users, polydrug users are a very stigmatized and marginalized group who may engage in more frequent high-risk drug use (51,52).…”
Section: Discussionmentioning
confidence: 99%